Model Penilaian Portofolio sebagai Upaya Meningkatkan Hasil Belajar IPS Terpadu - Muhammad Yogi Andrian Syah; Risma Dwi Arisona (JIIPSI: Jurnal Ilmiah Ilmu Pengetahuan Sosial Indonesia, 2021)
This study examines the Portfolio Assessment Model conducted in class VII MTs An-Najiyah. This study intends to determine the Integrated Social Studies portfolio assessment model in class VII MTs An-Najiyah with the teacher's focus on planning a portfolio assessment model, implementing a portfolio assessment model, and the results. It can also be interpreted as information on the extent to which Integrated Social Studies teachers carry out their duties as teachers, in carrying out their duties and carrying out their obligations as educating and educators, one of which is the portfolio assessment process which is very important for teachers, students, madrasas, and parents. The method used is a qualitative research method, field research which is a case study. Data collected by means of interviews, observation, and documentation. The data analysis carried out is qualitative analysis, among others, data reduction, data presentation, and drawing conclusions. This study resulted in information that (1) Planning for portfolio assessment is by preparing assessment components and assignments in the form of oral questions, multiple choice, descriptions, and concept map project assignments, before the assessment activity takes place, the teacher gives assignments spontaneously and sees the readiness condition of students. (2) The implementation of portfolio assessment is carried out by social studies teachers by paying attention to aspects of the task process and also the results, so the teacher will be able to control student behavior and student learning outcomes. (3) The results of the portfolio assessment are divided into two types, namely: process portfolio assessment and product portfolio assessment. By using the portfolio assessment method can improve the learning outcomes of Integrated Social Studies in class VII MTs An-Najiyah.